LEFT-SIDED TRAUMATIC DIAPHRAGMATIC INJURIES - Ivan Novakov (Science & Research, 2020)

(untitled)
Traumatic diaphragmatic injuries may result from either penetrating or blunt trauma, usually of the lower chest or upper abdomen. The injury of the left hemidiaphragm occurs three times more frequently than does injury to the right. The objective of this review is to present, on the base of personal experience, the mechanisms, diagnostic and therapeutic diaphragmatic injuries, the diagnostic algorithm and the management of these traumas that remains a challenge for the surgeon are presented.